Software Module Real-Time Target: Improving Development of Embedded Control System by Including Simulink Generated Code Into Existing Code - Netland, Øyvind; Skavhaug, Amund (EUROMICRO (IEEE Computer Society Press), 2013)
The method presented in this paper, Software module real-time target (SMRT), aim to make code generated by Simulink Coder easy to include into a real-time embedded code project. It is intended to give developers experienced in embedded programming better control and flexibility when using Simulink Coder, without having to understand the code generation process. A general methodology, SMRT, has been defined, and a library for using SMRT has been implemented for Xenomai Linux. The library can be modified for other operating systems. This solution has been tested on a Beagle bone development board and used in the development of a robot prototype.